Factor Affecting Female Students’ choice of Science, Technology, Engineering, and Mathematics (STEM) Career Choice: Literature Review - Sar, Monyrath (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
Science, Technology, Engineering, and Mathematics (STEM) career serves national economic development and respond to job market demands for maintaining/increasing productivity and international competitiveness in highly technological field of employment. Thus, this paper objectives to review previous research literatures about factors affecting female to participate in STEM careers and career development theories employed to promote female students’ choice of STEM careers. Based on literature review, women are highly underrepresenting in STEM field as a world-wide phenomenon because of factors such as personal factor and extra-person factor. Among six career development theories, Social Cognitive Career Theory (SCCT) (Lent & Hackett, 1987) emphasize both cognitive-person variable and extra-person variable which different from others five career developments theories. Therefore, SCCT is good fit theory for the study conduct in Cambodia which has string culture influence for females. Implications for enhancing female students’ participation in STEM careers were also discussed.